Integrated Supports for Women and Girls Experiencing Substance Use and Complex Needs - Katherine Flannigan; Lisa Murphy; Jacqueline Pei (SAGE Publishing, 2023)
There is strong research to support integrated and gender-sensitive harm reduction approaches for supporting women, girls, and gender diverse people. For individuals who are pregnant, flexible and integrated treatment approaches may be especially important. In this study, we report on an integrated program in rural Canada designed to support pregnant women, girls, and gender diverse people experiencing substance use and other complex needs. Program data (N = 393) from the 2nd Floor Women's Recovery Centre (2nd Floor) at the Lakeland Centre for Fetal Alcohol Spectrum Disorder (LCFASD) was analyzed with several aims. Study goals were to (1) describe characteristics and needs of clients, (2) identify factors associated with program completion, and (3) for a subset of clients, examine resources, wellbeing, and social and behavioral outcomes after treatment. Clients ( M age  = 27.4 years, range 15-64) presented at the 2nd Floor with complex medical and mental health needs, and experiences of significant socioenvironmental adversity. However, almost two-thirds (63.4%) successfully completed the program, which was more likely for clients who had stable housing at intake and a possible or confirmed diagnosis of FASD. After treatment, clients reported high levels of wellbeing, and most were connected to health care and community resources. In the year after program completion, clients who were contacted for follow-up maintained strong connection to resources and reported notable improvements in social and behavioral functioning. Many were working or volunteering, most were in stable home environments, rates of substance use and legal involvement were substantially reduced, and many clients were actively caring for their children. This study offers important findings to inform future research, practice, and policy for supporting health and wellbeing for women, children, families, and communities.